KETAHANAN BEBERAPA VARIETAS PADI TERHADAP PENGGEREK BATANG PADA EKOSISTEM SAWAH MASUKAN BAHAN ORGANIK DAN ANORGANIK - Nur Habiba Bahar; Sudirman Numba; Abdullah Abdullah (Percetakan Umi Toaha Makassar, 2020)
This study aims that knowing the level of resistance of several rice varieties to stem borer in organic and inorganic input paddy ecosystems. The research was conducted in the rice fields of Nonong Village, Batui District, Banggai Regency, from March to June 2020. The research used the Split Plot Design method. The main plot was the rice field ecosystem, namely organic input rice fields and inorganic input rice fields, while the subplots were 4 types of rice varieties, namely: Ciherang, Cisantana, Ciliwung and Towuti. Each treatment unit was repeated three times in order to obtain 24 experimental units. The results showed that the towuti variety planted in the paddy field ecosystem with inorganic input was more resistant to rice stem borer. The intensity of attack and the population of stem borer in the lowland organic matter input ecosystem was higher than the inorganic input lowland ecosystem. There is no interaction between rice varieties and types of paddy ecosystems (input of organic and inorganic materials) on the intensity of stem borer attack and the results of production